‘How am I supposed to enjoy that?’ Assemblages of porn spectatorship - Asman Ihsan Can (Taylor & Francis, 2025)
This article investigates the affective dynamics of porn spectatorship and assemblage formation connected to it through the experiences of the 18 study participants. By bringing conceptualizations of the ‘social’ and non-human agency from actor–network theory to porn studies, the article conceptualizes what porn consumption assembles and how certain sexual norms are materialized by being (affectively) experienced and lived, a process which eventually involves spectators’ different fantasies, interests, and preferences. The article asks what different entities, be they non-human or human, may ‘authorize, allow, afford, encourage, permit, suggest, influence, block, render possible, forbid’ in their material-semiotic heterogeneity and multiplicity within porn spectatorship.